2017
DOI: 10.1007/s00423-017-1550-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid minimally invasive esophagectomy vs. open esophagectomy: a matched case analysis in 120 patients

Abstract: Our retrospective analysis shows that reduction of postoperative pulmonary morbidity, perioperative blood loss, and shortening of hospital stay can be achieved by HMIE. The procedure is safe, and the rate of surgical complications and oncological radicality is comparable to the conventional procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 26 publications
6
47
1
3
Order By: Relevance
“…Given such concerns, we decided to perform hybrid MIE using thoracoscope. Compared with the study by Glatz and colleagues, who used hybrid MIE with laparoscope, our study showed a greater number of harvested lymph node and a notably lower number of pulmonary complications (17).…”
Section: Discussioncontrasting
confidence: 73%
“…Given such concerns, we decided to perform hybrid MIE using thoracoscope. Compared with the study by Glatz and colleagues, who used hybrid MIE with laparoscope, our study showed a greater number of harvested lymph node and a notably lower number of pulmonary complications (17).…”
Section: Discussioncontrasting
confidence: 73%
“…The results favored the hybrid procedure, with a lower complication rate (36% versus 64%, P < 0.001) and a trend toward a better 3‐year survival rate (67% versus 55%, P = 0.05). A retrospective study from Germany also showed a reduction in pulmonary morbidity, blood loss, and a shortening of hospital stay (14 versus 18 days, P = 0.002) in the hybrid group of 60 patients …”
Section: Minimally Invasive Techniquesmentioning
confidence: 90%
“…Although the full results have not been made available, major pulmonary complications were reported to be significantly less frequent in the hybrid group (30.1% versus 17.7%) in a recently published abstract by the American Society of Clinical Oncology . In combination with several case‐matched studies, these findings suggest that morbidity may already be reduced by only performing the abdominal phase minimally invasively . In this light, hybrid esophagectomy might be an option for surgeons in low‐volume centers who would face challenges in completing their thoracoscopic learning phase owing to insufficient caseload.…”
Section: Minimally Invasive Surgerymentioning
confidence: 84%